Clinical Outcomes of TECNIS Toric Intraocular Lens Implantation after Cataract Removal in Patients with Corneal Astigmatism - Waltz, Kevin L.; Featherstone, Kristen; Tsai, Linda; Trentacost, Debbie (Ophthalmology (Rochester, Minn.), 2015)
To evaluate safety and effectiveness of the TECNIS toric intraocular lenses (IOLs). Prospective, multicenter, 2-armed, bilateral, 6-month clinical trial following the American National Standards Institute (ANSI) standard for Toric IOLs. Subjects implanted with a TECNIS toric IOL (n = 172) or a TECNIS 1-piece control IOL (ZCB00; n = 93). Subjects underwent standard cataract surgery with IOL implantation. The randomized control arm consisted of subjects requiring cylinder correction of 0.75 to 1.50 diopters (D) who were implanted with either toric (ZCT150) or nontoric (ZCB00) IOLs. The open-label arm (OLA) consisted of subjects requiring cylinder correction of 1.50 to 3.62 D and implanted with ZCT225, ZCT300, or ZCT400 IOLs. Assessments were at 1 day, 1 week, and 1, 3, and 6 months and included uncorrected distance visual acuity (UCDVA) and best-corrected distance visual acuity (BCDVA), manifest refraction, keratometry, adverse events, spectacle use, and photographic documentation of IOL rotational stability. Mean percent reduction in cylinder (± standard deviation) was statistically significantly greater (P < 0.0001) for ZCT150 eyes (74.53±72.25%) versus ZCB00 eyes (31.61±78.73%). In the OLA, mean percent reduction in cylinder was 76.27±33.09%. A UCDVA of 20/20 or better was achieved by 43.6% (44/101) of ZCT150 eyes and by 23.7% (22/93) of ZCB00 eyes (P = 0.0026). In the OLA, 38.0% (27/71) achieved 20/20 or better UCDVA. Mean UCDVA was 0.10±0.14 for ZCT150 eyes and 0.16±0.16 for ZCB00 eyes (P = 0.0009); in the OLA, mean UCDVA was 0.11±0.12. The BCDVA was 20/40 or better for all eyes. Mean absolute lens rotation between visits for toric eyes pooled was less than 3°. Lens rotation of 5° or less occurred in 92.9% of toric eyes between 1 and 3 months and in 94.1% between 3 and 6 months, exceeding the ANSI standard for stability (≥90% of eyes with ≤5° of rotation between visits). Four lenses (2.3%) were repositioned during the study. The TECNIS toric IOLs successfully reduce ocular astigmatism and are a safe and effective treatment for cataract patients with corneal astigmatism.